1998
DOI: 10.1007/s004310050814
|View full text |Cite
|
Sign up to set email alerts
|

Differentialdiagnosis of neonatal adrenal haemorrhage and congenital neuroblastoma by colour coded Doppler sonography and power Doppler sonography

Abstract: Conventional colour coded Doppler sonography and power Doppler sonography are useful to differentiate between neuroblastoma and adrenal haemorrhage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 15 publications
(13 reference statements)
0
28
0
1
Order By: Relevance
“…In contrast to the peripheral rim-like calcifications and rim-like Doppler pattern of adrenal haemorrhage, neuroblastoma often shows a network of microscopic vessels with characteristic high-velocity Doppler shifts inside the tumour and stippled calcifications [7] . It has been suggested that many of the neonatal cases of neuroblastoma can regress spontaneously.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the peripheral rim-like calcifications and rim-like Doppler pattern of adrenal haemorrhage, neuroblastoma often shows a network of microscopic vessels with characteristic high-velocity Doppler shifts inside the tumour and stippled calcifications [7] . It has been suggested that many of the neonatal cases of neuroblastoma can regress spontaneously.…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation is the compression of the adrenal gland between the liver and spine and direct drainage of the right adrenal vein into the inferior vena cava inducing higher venous pressure changes compared to the left side where the adrenal vein connects to the renal vein [6] . The adrenal glands are particularly vulnerable to haemorrhage because of their size (about 20 times the relative size in the adult) and high vascularity with supply from the inferior phrenic artery, abdominal aorta and renal artery [7] .…”
Section: Discussionmentioning
confidence: 99%
“…As previously reported, postnatal ultrasonography examination was fundamental for diagnosis. Deeg et al described the main features that have to be taken into account, namely, the size of the mass, the presence of calcification, echogenicity (cystic, solid or heterogeneous), shape (round or triangular) and the characteristics of the connection with the adrenal gland and the kidney 7 . In our series, as in the literature, the solid nature of the tumor after birth (13 LRNBs among 17 solid tumors) and increasing size (6 LRNBs among seven growing tumors) favored the diagnosis of LRNB.…”
Section: Discussionmentioning
confidence: 99%
“…10 The absence of a large aberrant vessel does not rule out, however, the diagnosis of pulmonary sequestration, and color Doppler imaging cannot clearly distinguish between adrenal hemorrhage and hemorrhage occurring within a cystic NB. 7,[11][12][13][14] Computed tomography and MRI are highly contributory to the diagnosis of suprarenal masses when they show a systemic vessel of a sequestration. 10 Magnetic resonance imaging may show two different intensities within the mass, with debris-fluid levels suggesting intracystic hemorrhage, but again it is unable to distinguish between adrenal hemorrhage and hemorrhage occurring within a cystic LRNB.…”
Section: Discussionmentioning
confidence: 99%
“…the size of the mass, presence of calcification, echogenicity (cystic, solid or heterogenous), shape (round or triangular) and the characteristics of the connection with adrenal gland and the kidney. 6 Our patient had a suprarenal cystic tumor without any evidence of calcification.…”
Section: Discussionmentioning
confidence: 66%